Reference quality assembly of the 3.5-Gb genome of Capsicum annuum from a single linked-read library. Issue 1 (12th January 2018) - Hulse-Kemp, Amanda M; Maheshwari, Shamoni; Stoffel, Kevin; Hill, Theresa A; Jaffe, David; Williams, Stephen R; Weisenfeld, Neil; Ramakrishnan, Srividya; Kumar, Vijay; Shah, Preyas; Schatz, Michael C; Church, Deanna M; et al.
Abstract: Linked-Read sequencing technology has recently been employed successfully for de novo assembly of human genomes, however, the utility of this technology for complex plant genomes is unproven. We evaluated the technology for this purpose by sequencing the 3.5-gigabase (Gb) diploid pepper ( Capsicum annuum ) genome with a single Linked-Read library. Plant genomes, including pepper, are characterized by long, highly similar repetitive sequences. Accordingly, significant effort is used to ensure that the sequenced plant is highly homozygous and the resulting assembly is a haploid consensus. With a phased assembly approach, we targeted a heterozygous F1 derived from a wide cross to assess the ability to derive both haplotypes and characterize a pungency gene with a large insertion/deletion. The Supernova software generated a highly ordered, more contiguous sequence assembly than all currently available C. annuum reference genomes. Over 83% of the final assembly was anchored and oriented using four publicly available  de novo linkage maps. A comparison of the annotation of conserved eukaryotic genes indicated the completeness of assembly. The validity of the phased assembly is further demonstrated with the complete recovery of both 2.5-Kb insertion/deletion haplotypes of the PUN1 locus in the F1 sample that represents pungent and nonpungent peppers, as well as nearly full recovery of the BUSCO2 gene set within each of the two haplotypes. The most contiguous pepper genome assembly to date has been generated which demonstrates that Linked-Read library technology provides a tool to de novo assemble complex highly repetitive heterozygous plant genomes. This technology can provide an opportunity to cost-effectively develop high-quality genome assemblies for other complex plants and compare structural and gene differences through accurate haplotype reconstruction. Genomics: Linking up the pepper genome: A new method of genome sequencing, 'Linked Reads, ' has proven efficient and cost-effective in tests on a complex plant genome. Reference genomes have become the tool of choice for answering biological questions about crop species. However, existing methods of genome sequencing have drawbacks, particularly for large and complex plant genomes: older techniques tend to generate low-quality sequences, and newer ones are prohibitively expensive. A US team led by Amanda Hulse-Kemp and Allen Van Deynze of the University of California, Davis, USA, tested a novel 'Linked-Read' approach taken from human genomics on the pepper, Capsicum annuum . The method links together short fragments from the same larger section of DNA during sequencing. The resulting genome was more complete than any previous Capsicum sequence, and heralds the opportunity to obtain new, affordable genomic resources for plant breeding.